Improving text collations by local text resegmentation. - Dähne, Janis; Ritter, Jörg; Molitor, Paul (Digital Scholarship in the Humanities, 2025)
In almost all current approaches, the collation of large texts is applied to a fixed given segmentation of the two texts witnesses to be compared and consists of two consecutive steps. First, the segments of the two texts are aligned, and then the aligned segments are compared in detail. For larger manuscripts or books consisting of many pages, the segments are usually the paragraphs of the texts. When comparing two texts, where the second text is a revised version of the first, poor local alignments can arise. This occurs in places where paragraphs have been split into two smaller paragraphs to insert a new paragraph in between, or where several consecutive sentences have been moved from one paragraph to the previous or next paragraph. Most paragraph collation tools cannot handle these scenarios properly because they align each paragraph with at most one paragraph of the other text. In this paper, we discuss this problem in detail and present a heuristic for resegmenting the two texts to be compared in order to achieve a better collation.